Book order of William Ladd Taylor - Taylor, William Ladd, 1854-1926.
Book order from Taylor to Doubleday, McClure & Company.
Illustrator of Wellesley, Mass.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: Doubleday, McClure & Company; Illustrators